P058 A proof-of-concept study on the combination of repetitive transcranial magnetic stimulation and relaxation techniques in chronic tinnitus. Issue 3 (March 2017) - Kreuzer, P.; Poeppl, T.; Bulla, J.; Schlee, W.; Lehner, A.; Langguth, B.; Schecklmann, M.
Abstract : Background: Interference of ongoing neuronal activity and brain stimulation motivated this study to prove the concept of a combined treatment approach integrating repetitive transcranial magnetic stimulation (rTMS) and relaxation techniques in patients with chronic tinnitus. Methods: Forty-two patients received rTMS consisting of ten sessions of high-frequency left dorsolateral prefrontal cortex followed by low-frequency left temporo-parietal cortex stimulation in this one-arm proof-of-concept study. During low-frequency stimulation patients listened to different kinds of relaxation audios selected according individual preferences (classical music; instructions to muscle or breath relaxation, imaginary journey or hypnosis). Variables of interest were tinnitus questionnaires, tinnitus numeric rating scales, depressivity, and quality of life. Results were compared to results of historical control groups having received the same rTMS protocol (active control) and sham treatment (placebo) without relaxation techniques. Results: Drop-outs and adverse events were low. Responder rates (reduction in tinnitus questionnaire (TQ) score by at least 5 points ten weeks after treatment) were 44.7% in the study, 27.8% in the active control group, and 21.7% in the placebo group, differing between groups on a near-significant level. Combination of rTMS and relaxation showed higher amelioration in the tinnitus handicap inventory questionnaire (THI) in contrast to rTMS alone. Deepness of relaxation during rTMS and selection of active relaxation vs. passive listening to music predicted larger reductions in the TQ-score. All remaining secondary outcomes turned out non-significant. Discussion: Combining rTMS and relaxation techniques has proven to be a safe, feasible and promising approach to enhance rTMS treatment effects in chronic tinnitus.